Development of an innovative wireless power transmission model for marine applications - Farooq, Umar; Masood, Hajira; Suakaew, Jiropast; Wongpany, Kruawan; Pijitrojana, Wanchai (Journal of Applied Research on Science and Technology (JARST), 2024)
The conventional wired charging system for ship-to-shore charging of underwater vehicles is prone to specific problems related to unreliable connection mechanisms and safety. The wireless charging system overcomes the danger of electrocution, as the power is transferred from the shore to the ship via electromagnetic induction instead of traditional ways of transferring AC power in the marine environment. This paper presents a novel system-level modeling and designing of wireless power transmission for marine applications. The proposed system comprises three main components: (a) a shore-side mobile transmitter (Shore-SMT), (b) an onboard static receiver, and (c) another ship-side mobile transmitter (Ship-SMT). The Shore-SMT and Ship-SMT, each consisting of a circular array of magnets, rotate in the vicinity of the receiver with a fixed circular variety of coils, resulting in voltage induction in the receiver coil. Consequently, the induced voltage in the receiver coil charges the onboard batteries. COMSOL® MULTIPHYSICS environment is used for the modeling and simulation of the proposed system using finite element method (FEM). The test cases simulate the individual and mutual rotation of the transmitters at several distances from the receiver coil. A prototype of the model is also developed. Experimental results from the developed prototype show promising performance as the percentage of transferred voltage increases from a single layer of x9 coil and x9 magnet bars to 70-75% and 80% in a double layer of x9 Ferro bars with x9 winding coils and double-sided x12 magnets and x9 winding coils respectively. It proves to be a better alternative to the conventional methods used for Ships and Vessel charging.